(untitled) (Journal of Computational Mathematics, 1993)
A numerical method for singularly perturbed semilinear boundary value problems is given. The method uses the fourth order Hermite scheme on a special discretization mesh. Its stability and convergence are investigated in the discrete L^1 norm.